Blockade of Programmed Cell Death Protein-1 Pathway for the Treatment of Melanoma - Madhuri Bhandaru; Anand Rotte (Journal of Dermatologic Research And Therapy, 2017)
Metastatic melanoma is a very deadly type of skin cancer with poor prognosis and low 5-year survival rates. Until recently, patients with metastatic melanoma had very few treatment options, which only included dacarbazine and aldesleukin. In 2011, the first checkpoint blocker, ipilimumab was approved for the treatment of unresectable metastatic melanoma but its success was eclipsed by low response rates and high incidence of adverse events. Later in 2014, anti-PD-1 antibodies, nivolumab and pembrolizumab were approved for the treatment of metastatic melanoma. With comparatively high response rates and manageable safety profile, PD-1 blockers were remarkably successful in the treatment of melanoma and also other cancer subtypes such as non-small cell lung cancer and metastatic urothelial carcinoma. This article highlights the success of anti-PD-1 antibodies, discusses the mechanism of PD-1:PD-L1/2 pathway, responses of melanoma patients to PD-1 blockers and the research on improving response rates to PD-1 blockers.
Keywords: melanoma